2016
DOI: 10.1016/j.pedhc.2015.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Vaccination Policies Among Utah Pediatric Clinic Employees

Abstract: Vaccination of health care workers is an effective approach to reduce disease transmission. Mandatory vaccination policies can significantly improve vaccination rates among health care workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Children are considered as vectors for the spread of influenza (70,72). Healthcare workers (HCWs) are exposed to patients with influenza in the workplace; thus, they are at risk of occupationally-acquired influenza that may be transmitted to their patients and other colleagues, more frequently than the general population (68,69,73,74). It has been reported that the annual incidence of infection among unvaccinated HCWs is 3-fold higher than among those vaccinated (68,69,75).…”
Section: Paediatric Healthcare Workers and Vaccination Against Influenzamentioning
confidence: 99%
See 1 more Smart Citation
“…Children are considered as vectors for the spread of influenza (70,72). Healthcare workers (HCWs) are exposed to patients with influenza in the workplace; thus, they are at risk of occupationally-acquired influenza that may be transmitted to their patients and other colleagues, more frequently than the general population (68,69,73,74). It has been reported that the annual incidence of infection among unvaccinated HCWs is 3-fold higher than among those vaccinated (68,69,75).…”
Section: Paediatric Healthcare Workers and Vaccination Against Influenzamentioning
confidence: 99%
“…Thus far, the enforcement of mandatory immunization policies has achieved high coverage rates against influenza among paediatric HCWs (68). However, the most feasible practice seems to be the adoption of novel strategies and interventions that aim in changing behaviour against ‘vaccine hesitancy’, establishing scientific evidence and integrated health programme planning models (69,73,77). An increased coverage can be achieved when better information and education is given regularly to the staff and at the same time easy, free and scheduled access to the vaccination is provided (69,70,74,76).…”
Section: Paediatric Healthcare Workers and Vaccination Against Influenzamentioning
confidence: 99%
“…The original questionnaire was pretested in 12 outpatient clinics, including family and primary care clinics, and then adjusted according to feedback. The questionnaire was also utilized in another study involving pediatric clinics (Luthy et al, 2016) and was adjusted for the family practice environment. The questionnaire consists of six demographic, eight multiple choice, and four open-ended items.…”
Section: Instrumentmentioning
confidence: 99%